2008
DOI: 10.1093/sleep/31.3.395
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Actigraphy to Study Sleep Disorders in Preschoolers: Some Concerns about Detection of Nighttime Awakenings

Abstract: Actigraphy has poor agreement for detecting nocturnal awakenings, compared with video observations, in preschool-aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(142 citation statements)
references
References 26 publications
6
134
1
1
Order By: Relevance
“…The CSHQ is a 33 item questionnaire for children aged 4 to 12 years. It has also been used for younger children from the age of 2 onwards (Goodlin-Jones., Sitnick., et al, 2008). It has recently been administered in Hollway, Aman, and Butter (2013) and Mannion et al (2013).…”
Section: Objective Measures Used To Assess Sleepmentioning
confidence: 99%
“…The CSHQ is a 33 item questionnaire for children aged 4 to 12 years. It has also been used for younger children from the age of 2 onwards (Goodlin-Jones., Sitnick., et al, 2008). It has recently been administered in Hollway, Aman, and Butter (2013) and Mannion et al (2013).…”
Section: Objective Measures Used To Assess Sleepmentioning
confidence: 99%
“…Sitnick et al 19 showed that an algorithm commonly used with adults is too sensitive with a population of young children, resulting in high false negative rates (i.e., actigraphy detects wakefulness when the child is probably sleeping). In fact, although several studies with infants and children have reported that various actigraphy devices are highly correlated (> 80%) with PSG or videosomnography, 14,[16][17][18][19][20][21][22][23] most of these studies have shown very low ability to correctly identify wakefulness 14,17,19,22 and hence, sleep fragmentation. 24 Nevertheless, the American Academy of Sleep Medicine (AASM) states that the use of actigraphy in normal children and special pediatric populations is indicated for the assessment of sleep patterns and response to treatment.…”
mentioning
confidence: 99%
“…19 However, this algorithm has not been validated in preschoolers against PSG. The present study aims to compare the validity of three algorithms for detecting sleep with actigraphy by comparing them to PSG in preschoolers.…”
mentioning
confidence: 99%
“…Actigraphs are used to detect body movements using a build-in accelerometer and give indices of awakenings. A number of studies have been presented that focus on the detection of awakenings based on activity (Lotjonen et al, 2003;Paquet et al, 2007;Sitnick et al, 2008). The use of actigraphy as a sleep-wake indicator is subject to discussion (Pollak et al, 2001;Tryon, 2004).…”
Section: Automatic Detection Of Awakeningsmentioning
confidence: 99%
“…An important shortcoming of these methods is their failure to detect an awakening when a person lies immobile in bed. In some extreme cases even a transition from supine to sitting position can sometimes be undetected (Sitnick et al, 2008). During the course of the EASI project, an algorithm has been developed that is able to automatically detect every time the user is awake during the sleeping period (Bulckaert et al, 2010).…”
Section: Automatic Detection Of Awakeningsmentioning
confidence: 99%